Redescription of a few Filchneria Klapálek, 1908 (Plecoptera, Perlodidae) species on the type and fresh material - Teslenko, Valentina A.; Palatov, Dmitry M. (Zootaxa, 2023)
Five Filchneria Klapálek, 1908 (Plecoptera, Perlodidae) species known since the last century (F. balcarica Balinsky, F. mesasiatica Zhiltzova, F. irani (Aubert), F. kuenluensis (Šámal), and F. olgae (McLachlan)) were redescribed on types stored in museums in the Netherlands, Switzerland, Russia and newly acquired material. The redescription were in accordance with the requirements of modern taxonomy, illustrated with color photographs of the habitus, head, pronotal patterns, eversible male paraproct lobes, male paraproctal sclerite, aedeagus (as possible), details of chaetotaxy, female subgenital plate, and egg using digital cameras and SEM. The diagnostic features of each species are revealed. The main differences were established in the male paraproctal sclerite shape, in the posterior margin of tergum 10, the female subgenital plate, and the egg structures. After reexamining the syntype series of Filchneria olgae, a lectotype is designated for this species. Filchneria kuenluensis is proposed to transfer to Perlodinella Klapálek, 1912 with the valid name Perlodinella kuenluensis (Šámal, 1935) comb. nov. Filchneria shobhaae is considered as a junior synonym of Zhiltzovaia amabilis (Jewett, 1958) syn. nov.